Analisis Interaksi Penggemar Serial Animasi dalam Kolom Komentar YouTube - Ruth Ivanaomi; Christina Tri Hendriyani (Universitas Sebelas Maret (UNS), 2026)
comment section of the YouTube channel CHIBI MARUKO-CHAN - Bahasa Indonesia. The aim of this research is to describe the forms of interaction among fans, understand how they convey identity, values, and culture through comments, and identify the factors that drive these interactions. This study employs a mixed methods approach with a case study method within the pragmatism paradigm. Data were collected through documentation techniques using purposive sampling on three episodes with the highest interaction levels : episodes 598, 605, and 633, resulting in a total of 2.440 comments analyzed using thematic content analysis. Data validity was ensured through theory triangulation, specifically fan culture theory and symbolic interaction theory. The findings show that fan interactions include emotional expressions, social interactions, and cultural participation. Fans’ collective identity is reflected through statements positioning themselves as part of a group sharing similar childhood experiences. The fans values are seen in comments expressing moral views and attitudes toward the content. Culture is conveyed through interpretations and associations of cultural symbols in the series with other cultures beyond the show. The factors driving interaction include the role of media features and YouTube accessibility, emotional attachment to the series, childhood memories and nostalgia, a sense of togetherness, collective identity claims, engagement in discussion and opinion-sharing, and the influence of moral values portrayed in the series. Overall, this study affirms that the comment section is not merely a space for responding to content, but also a social arena where fans express emotions, construct identity, and co-produce shared knowledge and culture.